2020
DOI: 10.1136/bcr-2020-236509
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing variant of mucoepidermoid carcinoma: a diagnostic challenge

Abstract: The sclerosing variant of mucoepidermoid salivary gland carcinoma is extremely rare. It is nearly impossible to diagnose this condition preoperatively. We present a case of a 23-year-old woman with a 1-year history of left parotid enlargement with inconclusive fine-needle aspiration cytology results. MRI showed an irregular parotid mass, and subsequent partial parotidectomy confirmed the diagnosis. We discuss the diagnostic pitfalls of this condition and provide a review of the literature surrounding its patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, the histologic diversity of MECs has led to the recent acknowledgment of multiple variants, including Warthin-like, spindle cell, sclerosing, mucoacinar, ciliated, and other types. [9][10][11][12][13] Hence, pathologists need to be aware of the diverse morphologic spectrum of MEC and also acknowledge that unveiled variants of MEC present challenges for an accurate and prompt diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the histologic diversity of MECs has led to the recent acknowledgment of multiple variants, including Warthin-like, spindle cell, sclerosing, mucoacinar, ciliated, and other types. [9][10][11][12][13] Hence, pathologists need to be aware of the diverse morphologic spectrum of MEC and also acknowledge that unveiled variants of MEC present challenges for an accurate and prompt diagnosis.…”
mentioning
confidence: 99%
“…For example, Sams and Gnepp 7 emphasized the use of p63 immunostain in differentiating MEC from unusual acinic cell carcinoma with mucin production, and Sivakumar et al 8 also showed the beneficial usage of p63 and p40 in identifying myoepithelial and/or squamous differentiation in the salivary gland tumors. Furthermore, the histologic diversity of MECs has led to the recent acknowledgment of multiple variants, including Warthin-like, spindle cell, sclerosing, mucoacinar, ciliated, and other types 9–13 . Hence, pathologists need to be aware of the diverse morphologic spectrum of MEC and also acknowledge that unveiled variants of MEC present challenges for an accurate and prompt diagnosis.…”
mentioning
confidence: 99%